2016
DOI: 10.14214/sf.1323
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the Finnish mechanized tree-planting industry in 2013 and its success factors

Abstract: A survey of the Finnish mechanized tree-planting industry in 2013 and its success factorsLaine T., Kärhä K., Hynönen A. (2016). A survey of the Finnish mechanized tree-planting industry in 2013 and its success factors. Silva Fennica vol. 50 no. 2 article id 1323. 14 p. http://dx.doi. org/10.14214/sf.1323. Highlights• In 2013, 31 planting machines were operated by 22 businesses and planted 4.7 million seedlings on 2663 hectares in Finland.• Critical success factors included expertise of planting machine operato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Our key factors "High quality planting work" and "Education of operators" have previously been identified by Laine et al [8] as critical success factors for Finnish mechanized tree-planting contractors. Meanwhile, Mäkinen [34] concluded that for Finnish harvesting contractors, having only one client was a success factor.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Our key factors "High quality planting work" and "Education of operators" have previously been identified by Laine et al [8] as critical success factors for Finnish mechanized tree-planting contractors. Meanwhile, Mäkinen [34] concluded that for Finnish harvesting contractors, having only one client was a success factor.…”
Section: Discussionmentioning
confidence: 90%
“…In Finland, some of the corresponding information could be found from an interview study conducted in 2014 [8]. This information was updated via a Metsäteho-maintained online catalogue of Finnish mechanized tree-planting contractors [25], and two typical contractors were interviewed using a semi-structured method during the winter of 2017-2018.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations